A Bibliometric Analysis of Corporate Governance and Financial Performance: A Comparative Study Across Nations - Rachmat, Andi (LPPPIPublishing, 2025)
This study presents a comprehensive bibliometric analysis of research on corporate governance and financial performance across different nations. Using data retrieved from the database between 2000 and 2025, the study identifies key trends, influential authors, institutions, and countries contributing to the discourse. Through co-citation, co-authorship, and keyword co-occurrence mapping using VOSviewer, the findings reveal that corporate governance remains a critical determinant of firm performance, with growing emphasis on sustainability, transparency, and board diversity. The comparative approach highlights variations in research focus and theoretical perspectives among developed and developing economies. This study contributes to the existing body of knowledge by providing a global overview of the intellectual structure, research evolution, and emerging themes in the field of corporate governance and financial performance. The results are expected to guide future scholars, policymakers, and practitioners in understanding the dynamic relationship between governance mechanisms and financial outcomes in a cross-national context.